2021
DOI: 10.1136/bmjsem-2020-000996
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between duty factor and external forces in slow recreational runners

Abstract: ObjectivesRecreational runners show a large interindividual variation in spatiotemporal characteristics. This research focused on slow runners and intended: (1) to document the variance in duty factor (DF) between runners in a real-life running setting and (2) examine whether the interindividual variation in DF and stride frequency (SF) relates to differences in external loading parameters between runners.MethodsSpatiotemporal characteristics of 23 slow runners (ie, <2.6 m/s) were determined during a 5.2 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
4
10
1
Order By: Relevance
“…Indeed, DF and t f are related to the average vertical ground reaction force during t f (Beck et al, 2020) and effective vertical impulse during t f (Dorn et al, 2012), respectively. Both the average vertical ground reaction force during t f and effective vertical impulse during t f are proportional to the peak vertical ground reaction force, as supports the sine wave model of the vertical ground reaction force (Morin et al, 2005) and experimental data (Bonnaerens et al, 2021). The present study reported lower association between relative t c and DF values (correlations were moderate to high; Table 3 and Figure 4) than relative t c to DF values.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, DF and t f are related to the average vertical ground reaction force during t f (Beck et al, 2020) and effective vertical impulse during t f (Dorn et al, 2012), respectively. Both the average vertical ground reaction force during t f and effective vertical impulse during t f are proportional to the peak vertical ground reaction force, as supports the sine wave model of the vertical ground reaction force (Morin et al, 2005) and experimental data (Bonnaerens et al, 2021). The present study reported lower association between relative t c and DF values (correlations were moderate to high; Table 3 and Figure 4) than relative t c to DF values.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, it has received extensive attention as a nondrug antidepressant treatment. Studies have shown that running exercise 3 times a week for at least 8 weeks can achieve a therapeutic effect on patients with severe depression, and the intensity of the effect is about moderate to high; it was also found in animal experiments that running exercise can effectively improve the depression-like or anxiety-like behavior of experimental animals [ 4 ]. However, some people have put forward the opposite conclusion, they believe that running exercise has no antidepressant effect, and in the follow-up study of patients with depression, there is no significant improvement in the quality of life and disease severity of patients with depression [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SF was shown to be more variable in novice than expert runners, independently of the running speed (10 and 15 km/h) (Fadillioglu et al, 2022). Furthermore, Bonnaerens et al (2021) demonstrated that external forces were lower in recreational runners that run with higher DF and SF values (although non-significant for SF).…”
Section: Introductionmentioning
confidence: 91%